ChemInform Abstract: Nanodomain Cubic Cuprous Oxide as Reusable Catalyst in One‐Pot Synthesis of 3‐Alkyl/Aryl‐3‐ (pyrrole‐2‐yl/indole‐3‐yl)‐2‐phenyl‐2, 3‐dihydro‐isoindolinones in Aqueous Medium. Issue 41 (7th October 2014) - Sarkar, Swarbhanu; Chatterjee, Nivedita; Roy, Manas; Pal, Rammyani; Sarkar, Sabyasachi; Sen, Asish Kumar
Abstract This environmentally benign reaction proceeds via a domino Sonogashira‐5‐exo‐dig‐cyclization followed by regioselective addition of compounds (III) or (VI).